Case Report of a 27-year-old Patient with Hair Dye Poisoning Causing Acute Kidney Injury - B Jeevan Kumar; Devaki Kondaveeti; G Mounika; P Saraswathi; P Dharani Prasad; T Gokul (Journal of Forensic Science and Medicine)
Most suicides in India are brought on by ingesting poisons, with hair dye being the popular choice. Paraphenylenediamine (PPD) is the principal hazardous component of hair dye. Hair color hazardous effects are dose dependent and include acute kidney injury (AKI), metabolic acidosis, rhabdomyolysis, hypocalcemia, convulsions, and death. Here, we describe a notable instance of a young man with an AKI, pedal edema, oliguria, and epigastric burning sensation who has poisoned by hair dye. Proper supportive care, hemodialysis, and decreased serum creatinine had improved his health status. We are presenting this case to create awareness about hair dye poisoning and to know the importance of early recognition and appropriate management of toxicity.